River flow in the near future: a global perspective in the context of a high-emission climate change scenario - Müller, Omar Vicente (2023)
There is high confidence that global warming intensifies all components of the global water cycle. This work inves- tigates the possible effects of the global warming on river flows worldwide in the coming decades. We conducted 18 global hydrological simulations to assess how river flows are projected to change in the near future (2015-2050) compared to the re- cent past (1950-2014). The simulations are forced by runoff from HighResMIP-CMIP6 GCMs, which assume a high-emission scenario for the projections. The assessment includes estimating the signal-to-noise (S/N) ratio and the time of emergence (ToE) of all the rivers in the world. Consistent with the water cycle intensification, the hydrological simulations project a clear positive global river discharge trend from ∼2000, that emerges beyond the levels of natural variability and becomes ‘unfamil- iar’ by 2017 and ‘unusual’ by 2033. Simulations agree that the climate change signal is dominated by strong increases in flows of rivers originating in Central Africa and South Asia, and those discharging into the Arctic Ocean, partially compensated by the reduced flow projected for Patagonian rivers. The potential implications of such changes may include more frequent floods in Central African and South Asian rivers, driven by the projected magnification of the annual cycles with unprecedented peaks, a freshening of the Arctic Ocean from extra freshwater release, and limited water availability in Patagonia given the projected drier conditions of its rivers. This underscores the critical need for a paradigm shift in prioritizing water-related concerns, amidst the challenges of global warming.